MANFAAT BLACKBERRY BAGI WARTAWAN TRIBUN MANADO - Wangko, Bemmy Lerry (ACTA DIURNA KOMUNIKASI, 2013)
The Blackberry is very helpful and facilitates the work of the journalists, in particular. to get the news quickly and send them effectively. The news can be sent quicker without coming to the office, and without inthencing the quality of the news. Keyword : Blackberry, Journalist Work, News.